Statistical models for data analysis - Ingrassia, Salvatore; Vichi, Maurizio; Giudici, Paolo (Studies in Classification, Data Analysis, and Knowledge Organization, 2013)
The papers in this book cover issues related to the development of novel statistical models for the analysis of data. They offer solutions for relevant problems in statistical data analysis and contain the explicit derivation of the proposed models as well as their implementation. The book assembles the selected and refereed proceedings of the biannual conference of the Italian Classification and Data Analysis Group (CLADAG), a section of the Italian Statistical Society.